Studying Career Commitment of Indian Technology Professionals with the Moderating Effect of Perceived External Employability - Deshpande, Rohan; Chakraborty, Debarun (Prabandhan: Indian Journal of Management, 2023)
Purpose : This study aimed to assess the impact on Indian technology professionals’ career commitment through adverse career events such as career plateau and its manifesting factors. The key objectives of the study were: First, learn about the underlying factors that may have impacted ITians’ ability to curate sustainable career growth in IT; second, assay how these factors, in turn, could affect the overall IT career commitment; and third, analyze how perceived external employability could moderate the impact on career commitment. Methodology : A measurement model based on social cognitive theory, career plateau, and conservation of resources was designed. Three hundred sixty-one responses were received from Indian IT professionals using a structured questionnaire. SEM analysis was performed using AMOS to analyze the model’s and hypotheses’s validity. Findings : The results showed career commitment having a significant negative influence due to career plateau, the levels of which were alleviated when employees exhibited more vital growth aspirations coupled with a high sense of belief in their ability to acquire new skills and competencies continually. Practical Implications : This study provided a critical reference for employees to proactively curate career development strategies invigorating career commitment and long-term career growth prospects. It also generated insights for organizational policymakers to construct career development and training frameworks that could boost employee motivation, resulting in improved job engagement and productivity. Originality : To our knowledge, this is the first study to foray into analyzing the career commitment of Indian IT professionals and, as such, could serve as a robust foundation for future research on this topic, furthering knowledge of newer career patterns emerging in this sector.